(R)-fluoxetine enhances cognitive flexibility and hippocampal cell proliferation in mice. (April 2018) - Marwari, Subhi; Dawe, Gavin S
Fluoxetine is a clinically successful antidepressant. It is a racemic mixture of (R) and (S) stereoisomers. In preclinical studies, chronic treatment with fluoxetine (10 mg/kg) had antidepressant effects correlated with increased hippocampal cell proliferation in adult rodents. However, the contribution of the enantiomers of fluoxetine is largely unknown. We investigated the effects of treatment with (R)- and (S)-fluoxetine on cognitive behavioral paradigms and examined cell proliferation in the hippocampus of C57BL/6J female mice. In a behavioral sequencing task using the IntelliCage system in which discriminated spatial patterns of rewarded and never-rewarded corners were reversed serially, (R)-fluoxetine-treated mice showed rapid acquisition of behavioral sequencing (compared with S-fluoxetine) and cognitive flexibility in subsequent reversal stages in intra- and inter-session analysis. (R)-fluoxetine also increased cell proliferation in the hippocampus, in particular in the suprapyramidal blade of the dentate gyrus. (R)-fluoxetine had superior effects to (S)-fluoxetine in elevated plus maze, forced-swim and tail-suspension tests. These results suggest that (R)-fluoxetine, which has been reported to have a shorter half-life than (S)-fluoxetine, has superior antidepressant effects and more consistently improves spatial learning and memory. This profile offers advantages in depression treatment and may also aid management of the neurocognitive impairments associated with depression.